PENGELOLAAN KUALITAS AIR PEMELIHARAAN UDANG VANAME (Litopenaeus vannamei) MELALUI PEMBERIAN PROBIOTIK DI KECAMATAN MANYAR, KABUPATEN GRESIK - Satyantini, Woro Hastuti; Dewi, Nina Nurmalia; Isroni, Wahyu (Universitas Mataram, 2025)
Manyar Sub-district, located in Gresik, is home to many fish and shrimp pond farmers. Vannamei shrimp farming is a particularly popular aquaculture activity in Tanggul Rejo Village, Manyar Sub-district. However, the shrimp and fish farming industries face challenges in production, primarily due to diseases arising from declining water quality. Many pond farmers lack knowledge about the importance of water quality management to support successful shrimp farming, highlighting the need for appropriate technology to improve production. This study aimed to apply probiotics to manage the water quality of vannamei shrimp rearing media in Manyar Sub-district. The activity was carried out in several stages, including identifying and mapping the problems faced by farmers, delivering educational materials about the use of probiotics in shrimp farming, providing assistance for probiotic application, and monitoring and evaluating the results. The findings showed that the application of probiotics to the rearing water media every two days resulted in low ammonia and nitrite levels, as well as adequate oxygen levels and pH, which are conducive to vannamei shrimp cultivation.